Carcinomas of unknown primary localization with isolated unilateral lesion of axillary lymph nodes in women. - Poslavska, О. V.; Shponka, I. S.; Hritsenko, P. О.; Savchenko, P. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Among the most important achievements of recent decades in understanding the biology of cancers of unknown primary localization was the finding of favorable clinical and pathological subgroups occurring in 10-20%. Women with metastatic breast carcinoma, which affects only the axillary lymph nodes, represent a relatively small cohort of patients with long-term survival prospects. Objective. The aim is to investigate the complex of morphological, immunohistochemical and morphometric characteristics of carcinomas of unknown primary localization with lesions of isolated unilateral axillary lymph nodes in women in comparison with primary breast tumors to improve diagnostic algorithms. Methods. A retrospective analysis of the characteristics of biopsy material of 29 patients with unilateral lesion of isolated axillary lymph nodes without known primary tumor localization at the age of 32 to 86 years (mean 61.52 ± 14.42, median 60) and 48 observations of the postoperative material of patients with primary a breast tumor at the age of 30 to 89 years (mean 55.43 ± 12.19, median 56) for the period 2015 - 2017. Results. Carcinoma of unknown primary localization with unilateral lesion of isolated axillary lymph nodes in women revealed a significant advantage of Cytokeratin, Pane AE1, AE3 + / cytokeratin 7 + / ER + / PGR + / Her-2-new cases of metastatic carcinomas with the mammary phenotype. Like the primary breast tumors, the metastatic carcinomas had a morphological structure, as well as the area, perimeter and roundness of the nuclei (all p <0.05), but differed in the phenotypic distribution of the combination of prognostic markers of the "gold standard" ER, PGR, Her-2- new (p = 0.03746). Conclusions. With the decrease in the degree of differentiation, the primary and metastatic AK of the mammary gland can acquire a "triple-negative" status, given the high percentages of adenocarcinomas and undifferentiated cancers among the observations (28% and 10%, respectively), the immunohistochemical panel needs to be expanded with organ-specific breast markers and exclusion markers.